LA UBICACIÓN DE TRAMPAS Y FACTORES CLIMÁTICOS AFECTAN EL MONITOREO DE DESCORTEZADORES EN EL SUR DEL ESTADO DE JALISCO - Villa Castillo, Jaime; Villa Castillo, José (Revista Mexicana de Ciencias Forestales, 2020)
This study was carried out to fulfill the following questions: 1) If the position of traps within the bark-beetle spot would affect the number of trapped insects?, 2) How climatic factors can affect the number of insects trapped in pheromone-baited traps?, and 3) How the number of gathered insects is related to the infestation level?. This experiment consisted on recording the number of bark-beetle adults attracted toward frontalure-baited traps, from late april to middle december of 1992. Maximum and mínimum temperatures and rainfall were recorded. AJso, the number of infested trees was registered on three dates. The trap located near to recently infested trees attracted significantly more insects than other traps. Therefore, records of that trap were used to detennine climatic factors affecting the number of gathered insects. On this regard, maximum temperature and rainfalJ explained 89% of the variability on the number of insects. To the beginning of the study, the ratio of trapped insects: infested trees was 5: 1, whereas on both the middle and the end of the experiment such a ratio was 3: 1. A discussion about the interpretation of data on a monitoring approach is provided.